Observations on Health Information in Developing Countries - Hull, C. (Methods of Information in Medicine, 1994)
Based on personal experiences, observations are offered on health information in developing countries, ways in which information systems can be strengthened, and opportunities for health-information science graduates. Although data collection consumes a significant portion of the health worker’s day, information systems are often a low priority in developing countries. Health-information systems can be strengthened by focusing on local solutions, by building skills in health workers, by utilizing appropriate technology, and by integrating information systems into health programs. Health-information science graduates can assist in improving systems in developing countries, but this will require a broad and flexible definition of health information science, which is much more than computing technology; it is supporting health workers to define, manage, and apply the information they need.
Keywords: Information Systems; Developing Countries; Health-Information Science